2004
DOI: 10.1097/01.prs.0000131016.12754.30
|View full text |Cite
|
Sign up to set email alerts
|

Applications of a Mouse Model of Calvarial Healing: Differences in Regenerative Abilities of Juveniles and Adults

Abstract: Young children are capable of healing large calvarial defects, whereas adults lack this endogenous osseous tissue-engineering capacity. Despite the important clinical implications, little is known about the molecular and cell biology underlying this differential ability. Traditionally, guinea pig, rabbit, and rat models have been used to study the orchestration of calvarial healing. To harness the research potential of knockout and transgenic mice, the authors developed a mouse model for calvarial healing. Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
14

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 9 publications
4
89
0
14
Order By: Relevance
“…Thus, the CSD created on the bony vault of the cranium (calvaria) represents a severe test for bone graft substitutes. CSDs in the calvaria have been established for different mammalian species [9][10][11][12][13][14]. Modelling on parietal bone has been applied on rats from different strains and at various ages [10,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the CSD created on the bony vault of the cranium (calvaria) represents a severe test for bone graft substitutes. CSDs in the calvaria have been established for different mammalian species [9][10][11][12][13][14]. Modelling on parietal bone has been applied on rats from different strains and at various ages [10,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…4 CSDs in the calvaria have been established for different animal species. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] The rat calvarial model offers advantages: the parietal bone is a large plate that facilitates the operation and the analysis (histology, imaging), no implant fixation is required, and the costs are limited in comparison with large animal models. Furthermore, as this experimental approach is widely used, a precise comparison of different grafted materials is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Sparing the dura mater is in fact critically important since several studies have shown that the dura is instrumental in bony regeneration of the skull. 1,35,117 As previously noted, humans up to 2 years of age have the capacity to spontaneously heal cranial defects that would be "critical" in an adult human. In 2003, Aalami et al 1 reported similar findings in a mouse model of juvenile and adult cranial defect healing: in the juvenile mice (6 days old) a significantly greater portion of critical-size calvarial defects was healed than in the adults (60 days old).…”
Section: Small-animal Modelsmentioning
confidence: 88%
“…Additionally, sophisticated molecular and cellular biology analytical tools are readily available and yield highly reproducible results. 1 In the mouse, a critical-size cranial defect is defined as a bony deficit greater than or equal to 5 mm. 63,67,80 Such a defect, if left untreated, will not heal in the life of an animal.…”
Section: Small-animal Modelsmentioning
confidence: 99%